Galápagos: World’s End - Beebe, William (1924)
Contains eighty-three black and White half-tone illustration as well as twenty-four illustrations on nine color plates. It is printed on high-grade paper in quarto volume and has a beautiful back and fore lining. The special author’s autograph edition comprises.